Survei Minat Siswa dalam Mengikuti Kegiatan Ekstrakurikuler Pembelajaran Bola Voli di Sekolah Menengah Atas Belitang Hulu Kabupaten Sekadau - sumarni, ilesa (Journal Sport Academy, 2024)
This study aims to determine students’ interest in participating in sports extracurricular activities at SMA Negeri 1 Belitang Hulu, Sekadau Regency. The research method used in this study was quantitative descriptive with a survey research design. The population of this research consisted of all students participating in the volleyball extracurricular activity at SMA Negeri 1 Belitang Hulu, Sekadau Regency. The research sample comprised 38 students, selected using a total sampling technique. Data collection techniques included direct observation and documentation, while the data collection instrument was a questionnaire. The results of the study showed that students’ interest in participating in volleyball extracurricular activities at SMA Negeri 1 Belitang Hulu, Sekadau Regency was influenced by both intrinsic and extrinsic factors. The intrinsic factors included: attention, which was in the “fair” category (42%); enjoyment, in the “fair” category (42%); and activity, in the “fair” category (47%). The extrinsic factors included: the coach, in the “fair” category (68%); facilities, in the “fair” category (45%); family, in the “fair” category (34%); and environment, in the “fair” category (37%).